THAIFAH: KOMUNITAS SOSIAL DALAM AL-QUR’AN - Ahmad Mujahid (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2017)
Term thaifah is one of the terms used by the Qur'an to designate social communities. This thaifah term is used in the Qur'an 26 times in various forms of derivation. Some of these verses are classified into groups of verses makkiyah and some others belong to the group of verses of madaniah. The search for these verses can be summarized as concluding that their use in the Qur'an refers to the meaning of small social groups that are part of large-scale social community, but sometimes it is also used to designate a social community identical to the social community that Appointed by term qaum. The term thaifah is one of the terms that point to the meaning of social community that is bound and unified by a particular social glue, that is, first, based on the religious and spiritual-transcendental dimension and ethics, both based on the intellectual and social-social dimension.